A new genus of the family Panfiloviidae (Insecta, Neuroptera) from the Middle Jurassic of China. (16th January 2013) - YANG, QIANG; MAKARKIN, VLADIMIR N.; REN, DONG
Abstract : Abstract:  Epipanfilovia oviformis gen. et sp. nov. (Neuroptera: Panfiloviidae) is described from the Middle Jurassic locality of Daohugou (Inner Mongolia, China) based on six specimens. A revised diagnosis of this family is provided. It includes two genera, Panfilovia Makarkin and Epipanfilovia gen. nov.; Osmylogramma Ponomarenko is removed from the family. Panfiloviidae is most closely related to another Jurassic family Grammolingiidae, and both are provisionally assigned to the superfamily Osmyloidea.